Disability Rights and the American Social Safety Net - Erkulwater, Jennifer L. (Book collections on Project MUSE., 2006)
"The recent history of the American welfare state has been viewed with dismay by those on the left because of the steady contraction of benefits under both Republican and Democratic administrations. In contrast, Jennifer L. Erkulwater describes the remarkable success of advocacy for the disabled at a time when the federal government was seemingly impervious to liberal policy inovations."--Jacket